Soluble CD163 Is a Predictor of Mortality in Patients With Decompensated Cirrhosis - Zhang, Yue; Huang, Chenkai; Nie, Yuan; Liu, Qi; Xiao, Nanxi; Liu, Linxiang; Zhu, Xuan (Frontiers in Medicine, 2021)
Background: Soluble CD163 (sCD163) is a scavenger receptor membrane protein expressed almost exclusively on Kupffer cells and other macrophages. It was found to be associated with the severity of liver cirrhosis. The aim of the present study was to determine whether the novel biomarker sCD163 predicts outcomes in patients with decompensated cirrhosis. Materials and methods: A single-center, observational, prospective study with 345 decompensated cirrhosis patients was conducted in the Gastroenterology Department between January 2017 and December 2020. Their plasma samples were tested by enzyme-linked immunosorbent assay (ELISA) for sCD163 within 24 hours of admission. These patients were followed up at 28 days, 3 months and 6 months. The independent risk factors were identified with uni- and multivariate logistic regression analyses. We evaluated the predictive performance of the new scoring system (including sCD163) and the original scoring system. Results: The sCD163 level was significantly higher in nonsurviving patients than in surviving patients. Positive associations were found between sCD163 levels and the Child-Turcotte-Pugh (CTP), Model for End-Stage Liver Disease (MELD) and albumin-bilirubin (ALBI) scores. Logistic regression confirmed that sCD163 was an independent risk factor for 28-day, 3-month, and 6-month mortality. The areas under the receiver operating characteristic curves (AUROCs) of the use of sCD163 for the prediction of 28-day, 3-month, and 6-month mortality were relatively higher (AUROCs: 0.856; 0.823 and 0.811, respectively). The AUROCs of the new scores obtained by adding sCD163 to the original scoring systems (CTP+sCD163, MELD+sCD163 and ALBI+sCD163) showed that the new scoring systems had better predictive performance than the original scoring systems at all time points (P<0.001). Conclusion: sCD163 is a prognostic predictor of short-term and long-term outcomes in decompensated cirrhosis patients. Accordingly, the addition of sCD163 to the original clinical scoring systems improved their prognostic performance.